Night vision camera system for intruder detection in indoor and outdoor environment - Sak, Jenn Shin (2015)
This project presents the detection of intruder existence by using a night vision camera system in indoor and outdoor environment. The entire project is done by using image processing techniques via OpenCV which run on Linux environment. The challenge of this project focuses on the detection ability of intruder by using a webcam at a fixed distance in low light condition. The histogram is generated to show the tonal variations and distribution of every frame of the images. Intruders can be detected by detecting the changes occur in the foreground image and the changes of histogram from the real-time video streaming through the webcam.